ChemInform Abstract: Anionic Amido/Carbocyclic Carbene Ligated Palladium(II) Complex for Room Temperature Suzuki Reaction. Issue 34 (1st August 2013) - Kantam, M. Lakshmi; Parsharamulu, T.; Likhar, Pravin R.; Srinivas, P.
Abstract The multi‐functional and stable title complex is employed for C‐C coupling reactions of deactivated aryl halides with boronic acids.